Pengaruh Variasi Arus Pengelasan SMAW Terhadap Hasil Uji Impak Dan Kekuatan Bending Pada Baja ST-41 (Universitas Islam 45 Bekasi, Fakultas Teknik, Jurusan Teknik Mesin, 2025)
This study aims to determine the effect of welding current variations on the toughness value of ST-41 steel welded joints using the Shielded Metal Arc Welding (SMAW) method. The welding process was carried out using a 2.6 mm diameter E6013 electrode with current variations of 90A, 100A, and 110A. Impact testing was performed on nine specimens, with three specimens for each current variation, using the Charpy test method. The test results showed that 100A current produced the highest impact value with an average of 1.96 Joule/mm², followed by 110A (1.91 Joule/mm²), and 90A (1.85 Joule/mm²). These results indicate that the welding current affects the material toughness, and 100A is the optimal current in the welding process of ST-41 steel to achieve maximum weld joint toughness.